North American members of the reticulata-like species group of the water mite genus Kongsbergia (Acari: Hydrachnidiae: Aturidae) - Radwell, Andrea J.; Smith, Ian M. (Zootaxa, 2012)
Fifteen North American species of the water mite genus Kongsbergia, 11 of which are new to science, are described andallocated to the newly proposed reticulata-like species group. This group is characterized by synapomorphic contours ofthe dorsal shield in males in the form of symmetrical ridges, an elevated hump anteromedially and a marked depressionposteromedially that bears a medial ridge with the excretory pore at its posterior end. These species are further assigned to six subgroups diagnosed by various shared derived character states of males. Adults of K. reticulata Habeeb, 1956, K.reticulata labyrintha Habeeb, 1957, and K. cyanea Habeeb, 1981 are redescribed based on examination of types and ad-ditional specimens, and all are recognized as full species. The description of adults of K. robisoni Radwell and Smith,2011, is revised slightly based on observations on specimens from recently discovered populations. Adults of 11 new spe-cies are described including K. appalachiana sp. nov., K. atkinsonae sp. nov., K. cooki sp. nov., K.crista sp. nov., K. crum-pae sp. nov., K. humeralis sp. nov., K. floridana sp. nov., K. laurentiana sp. nov., K. setosa sp. nov., K. texana sp. nov., and K. transversa sp. nov.. Distributional data and a key to males for these species are presented.